Short communicationCoronary stent entrapment - Macovei, Liviu Gheorghe; Presura, Razvan Mihai; Anghel, Larisa; Stanciu, Bogdan; Lovin, Nicusor; Haret, Roberto; Arsenescu-Georgescu, Catalina (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
A 64-year-old woman with a history of coronary artery bypass and coronary angioplasty with unexpanded stent entrapment blocked in the circumflex coronary artery and left main is now presenting with crescendo angina pectoris. The Department of Cardiovascular Surgery established that a new surgical intervention presents a very high risk. In this condition, we decide for elective percutaneous coronary intervention for stent restenosis, which is a very difficult procedure in the particular condition of unexpanded stent blocked in the circumflex coronary artery and left main.